Positive electrode active material for lithium ion secondary battery and method for producing same

The production of a positive electrode active material with a lithium tungstate or lithium molybdate coating on lithium metal composite oxide particles addresses high resistance and low discharge capacity issues in lithium ion secondary batteries, achieving improved conductivity and capacity maintenance.

JP7621066B2Active Publication Date: 2025-01-24SUMITOMO METAL MINING CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020077356
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-18
Filing Date
2020-04-24
Publication Date
2025-01-24
Estimated Expiration
2040-04-24

AI Technical Summary

Technical Problem

Existing lithium ion secondary batteries face issues with high positive electrode resistance and low discharge capacity maintenance due to the reaction between the lithium ion conductive solid electrolyte and the positive electrode active material, leading to hindered lithium ion diffusion and deteriorated output characteristics.

Method used

A method for producing a positive electrode active material with a coating layer containing lithium tungstate or lithium molybdate on the surface of secondary particles, formed by mixing a base material powder of lithium metal composite oxide with tungsten or molybdenum compounds, ensuring an average thickness of 3 to 150 nm and a variation index of 15% or less, to reduce interfacial resistance.

Benefits of technology

The method results in a positive electrode active material with low resistance and high discharge capacity maintenance, enhancing the performance of lithium ion secondary batteries by improving lithium ion conductivity and reducing interfacial resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621066000003
    Figure 0007621066000003
  • Figure 0007621066000001
    Figure 0007621066000001
  • Figure 0007621066000002
    Figure 0007621066000002
Patent Text Reader

Abstract

To provide: a positive electrode active material for a lithium ion secondary battery, which is low in positive electrode resistance and high in discharge capacity retention rate when used for a lithium ion secondary battery, and a method for producing the same; and a lithium ion secondary battery having a positive electrode containing the positive electrode active material for a lithium ion secondary battery.SOLUTION: There is provided a positive electrode active material for a lithium ion secondary battery in which base material powder is used as a raw material, the base material powder containing a secondary particle formed by the aggregation of primary particles of a lithium metal composite oxide that contains lithium, nickel and cobalt. A coating layer containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate is formed on the surface of the secondary particle. The average thickness of the coating layer is 3-150 nm, and the coefficient of variation (CV%) showing a variation in the thickness of the coating layer is 15% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a manufacturing method thereof, and more particularly to a positive electrode active material for a lithium ion secondary battery that has low positive electrode resistance and a high retention rate of discharge capacity when used in a lithium ion secondary battery, a manufacturing method thereof, and a lithium ion secondary battery having a positive electrode containing the positive electrode active material for a lithium ion secondary battery. [Background technology]

[0002] In recent years, environmentally friendly vehicles, such as hybrid vehicles and plug-in hybrid vehicles, that emit less carbon dioxide, have become more common from the viewpoint of protecting the global environment. Among the batteries used in environmentally friendly vehicles, the development of lithium-ion secondary batteries is desired because of their excellent output characteristics and charge / discharge cycle characteristics.

[0003] Known lithium ion secondary batteries are non-aqueous electrolyte secondary batteries using organic solvent electrolytes (electrolytic solutions) and all-solid-state batteries using non-flammable solid electrolytes. However, non-aqueous electrolyte secondary batteries using organic solvent electrolytes (electrolytic solutions) require safety measures because they are flammable. In contrast, all-solid-state batteries using non-flammable solid electrolytes have the advantage that they do not require safety measures like organic solvent electrolytes (electrolytic solutions) because the solid electrolyte is non-flammable.

[0004] An all-solid-state battery using a non-flammable solid electrolyte is composed of a positive electrode, a negative electrode, and a lithium ion conductive solid electrolyte. The active materials of the positive and negative electrodes are generally made of materials capable of desorption and insertion of lithium. Among all-solid-state batteries using such materials, all-solid-state batteries using layered or spinel-type lithium metal composite oxides as the positive electrode active material are expected to have high energy density because they can obtain an electromotive force of 4.5 V or more. However, the all-solid-state battery has a drawback in that the lithium ion conductive solid electrolyte and the positive electrode active material react at the interface between them to form a heterogeneous interface, which prevents the diffusion of lithium ions at the heterogeneous interface, thereby increasing the electrical resistance and decreasing the output characteristics of the battery.

[0005] As a coated active material capable of suppressing an increase in the interface resistance between an active material and a solid electrolyte material, a coated active material has been proposed that has an active material and a coating layer that coats the active material, the coating layer being composed of a material containing elemental tungsten (see, for example, Patent Document 1). The coated active material contains LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 A rolling flow coating method using simple tungsten and a tungsten compound as a coating material is used as a means for forming a resistance reducing layer on the surface of the base powder.

[0006] In addition, a positive electrode active material for a non-aqueous electrolyte secondary battery, which can suppress gelation of a positive electrode composite paste, can maintain battery capacity when used in a secondary battery, has high output characteristics, and is excellent in charge-discharge cycle characteristics, is provided, which comprises a lithium metal composite oxide powder having a layered crystal structure, and the lithium metal composite oxide powder is represented by the formula: Li s Ni 1-x-y-z Co x Mn y M z O 2+α(where 0.05 ≦ x ≦ 0.35, 0 ≦ y ≦ 0.35, 0 ≦ z ≦ 0.10, 1.00 < s < 1.30, 0 ≦ α ≦ 0.2, M represents at least one element selected from the group consisting of V, Mg, Mo, Nb, Ti, W, and Al), containing secondary particles formed by aggregation of primary particles and a second compound containing lithium, wherein the second compound is present on the surface of the primary particles, and is a compound formed by reacting at least one first compound selected from the group consisting of an oxide containing no lithium, a hydrate of the oxide, and an inorganic acid salt containing no lithium with lithium ions in the presence of water. There has been proposed a positive electrode active material for a non-aqueous electrolyte secondary battery in which the pH of the supernatant after dispersing 5 g of the positive electrode active material in 100 mL of pure water and allowing it to stand for 10 minutes is 11 to 11.9 at a temperature of 25°C (see, for example, Patent Document 2).

[0007] Also, in all-solid-state batteries, as a means for suppressing the reaction between a sulfide-based solid electrolyte and LiCoO 2 and reducing the interfacial resistance, a method has been proposed in which the surface of LiCoO 2 particles of the base material powder is coated with a metal alkoxide as a coating raw material and compounds such as Li 2 SiO 3 , LiNbO 3 , LiTaO 3 are coated using the sol-gel method (see, for example, Non-Patent Documents 1 to 3).

[0008] However, in the inventions described in Patent Documents 1 to 2 and Non-Patent Documents 1 to 3, since an excess lithium compound such as lithium hydroxide is contained on the surface of the particles of the lithium metal composite oxide constituting the base material powder, when a positive electrode composite material paste is prepared using the lithium metal composite oxide, the lithium compound may elute into the solvent contained in the positive electrode composite material paste, and the positive electrode composite material paste may gel.

[0009] Furthermore, as described in Patent Document 1 and Non-Patent Documents 1 to 3, when the tumbling flow coating method using tungsten or a tungsten compound as the coating raw material or the sol-gel method using a metal alkoxide as the coating raw material is adopted as a method for forming a resistance-reducing layer on the particle surface of the base powder, the cost of the raw material and the cost required for the coating process are high, making it impossible to produce lithium-ion secondary batteries on an industrial scale.

[0010] In the inventions described in Patent Documents 1 and 2, when an excess lithium compound is used as a lithium supply source for the coating compound, if the amount of coating raw material such as a tungsten compound or molybdenum compound added is relatively small compared to the amount of the lithium compound, the resulting positive electrode composite paste will gel, whereas if the amount of coating raw material added is relatively large compared to the amount of the lithium compound, even the lithium necessary for the base powder itself, which constitutes the composite oxide together with nickel, cobalt, etc., will be taken away, and there is a risk that the performance as a positive electrode active material will not be fully exhibited.

[0011] Furthermore, in the invention described in Patent Document 2, when determining the amounts of compounds such as a tungsten compound and a molybdenum compound to be added as coating raw materials, a test positive electrode active material is first produced using a small amount of base material powder and coating raw materials, and a complicated preliminary experiment is required to confirm the amounts of the compounds required for making the pH of a slurry of the positive electrode active material fall within a predetermined range. This makes it impossible to efficiently produce lithium ion secondary batteries on an industrial scale. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] International Publication No. 2012 / 105048 [Patent Document 2] International Publication No. 2017 / 073238 [Non-patent literature]

[0013] [Non-Patent Document 1] Chemistry of Materials, Vol. 22, 2010, pp. 949-956 [Non-Patent Document 2] Electrochemistry Communications, Vol. 9, 2007, pp. 1486-1490 [Non-Patent Document 3] Solid State Ionics, Vol. 179, 2008, pp. 1333-1337 Summary of the Invention [Problem to be solved by the invention]

[0014] The present invention has been made in view of the above-mentioned conventional techniques, and an object of the present invention is to provide a positive electrode active material for lithium ion secondary batteries which has low positive electrode resistance and a high retention rate of discharge capacity when used in lithium ion secondary batteries, a method for producing the same, and a lithium ion secondary battery having a positive electrode containing the positive electrode active material for lithium ion secondary batteries. [Means for solving the problem]

[0015] The present invention ,original A method for producing a positive electrode active material for a lithium ion secondary battery using a base powder containing secondary particles formed by agglomeration of primary particles of a lithium metal composite oxide containing lithium, nickel, and cobalt as a starting material, comprising the steps of: The lithium metal composite oxide has the formula (I): Li s Ni 1-x-y Co x M y O 2+α (I) (In the formula, s, x, y and α are numbers satisfying 1.00≦s≦1.30, 0.05≦x≦0.35, 0≦y≦0.45 and −0.1≦α≦0.2, respectively, and M represents Al.) a coating layer containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate is formed on a surface of the secondary particles, the coating layer has an average thickness of 3 to 150 nm, and a coefficient of variation (CV%) indicating the variation in thickness of the coating layer is 15% or less; A first mixture is prepared by mixing the base material powder and water so that the water content in the mixture of the base material powder and water is 4 to 7 mass %; The temperature of the first mixture obtained above is adjusted to 25 to 50°C, and the first mixture is mixed with a coating raw material to prepare a second mixture; The method includes a step of drying the second mixture obtained above at a temperature of 150 to 250 ° C. to form a coating layer on the surface of the secondary particles contained in the base powder, thereby producing a positive electrode active material; A coating raw material containing at least one compound selected from the group consisting of a tungsten compound and a molybdenum compound is used as the coating raw material, At least one tungsten compound selected from the group consisting of tungsten oxide, tungstic acid, and ammonium tungstate is used as the tungsten compound, and at least one molybdenum compound selected from the group consisting of molybdenum oxide, molybdic acid, and ammonium molybdate is used as the molybdenum compound, The total amount of tungsten and molybdenum per 100 parts by mass of the base material powder is adjusted to 0.1 to 6 parts by mass. Ruri The present invention relates to a method for producing a positive electrode active material for a lithium ion secondary battery. Effect of the Invention

[0016] According to the present invention, there are provided a positive electrode active material for lithium ion secondary batteries which has low positive electrode resistance and high retention rate of discharge capacity when used in lithium ion secondary batteries, a method for producing the same, and a lithium ion secondary battery having a positive electrode containing the positive electrode active material for lithium ion secondary batteries. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic diagram illustrating one embodiment of a positive electrode active material for a lithium ion secondary battery according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The positive electrode active material for lithium ion secondary batteries and the manufacturing method thereof according to the present invention, as well as the lithium ion secondary battery having a positive electrode containing the positive electrode active material for lithium ion secondary batteries, will be described in detail below. The present invention is not limited to the embodiments described below, and the embodiments can be modified based on the knowledge of those skilled in the art without departing from the spirit of the present invention.

[0019] 1. Positive electrode active material for lithium-ion secondary batteries As described above, the positive electrode active material for a lithium ion secondary battery of the present invention is a positive electrode active material for a lithium ion secondary battery in which a base powder containing secondary particles formed by agglomeration of primary particles of a lithium metal composite oxide containing lithium, nickel, and cobalt is used as a raw material.

[0020] The positive electrode active material for lithium ion secondary batteries of the present invention has a feature in that a coating layer containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate is formed on the surface of the secondary particles, the average thickness of the coating layer is 3 to 150 μm, and the coefficient of variation (CV%) indicating the variation in thickness of the coating layer is 15% or less. Since the positive electrode active material for lithium ion secondary batteries of the present invention has the above-mentioned constituent requirements, it exhibits excellent effects of low positive electrode resistance and high retention rate of discharge capacity when used in a lithium ion secondary battery.

[0021] As a raw material for a positive electrode active material for a lithium ion secondary battery, a base powder containing secondary particles formed by agglomeration of primary particles of a lithium metal composite oxide containing lithium, nickel, and cobalt can be used.

[0022] (1) Base material powder A method for preparing the base powder is described below, but the present invention is not limited to this preparation method. The base powder contains secondary particles formed by aggregation of primary particles of lithium metal composite oxide. The base powder may inevitably contain a small amount of primary particles of lithium metal composite oxide.

[0023] As raw materials for the secondary particles of the lithium metal composite oxide that constitutes the base powder, lithium compound particles, nickel compound particles, cobalt compound particles, and, if necessary, additive metal M particles can be used.

[0024] (a) Preparation of metal composite hydroxide (precursor) particles [Crystallization] First, an aqueous solution of a metal compound containing nickel, cobalt, and, if necessary, an additive metal M such as manganese or aluminum is prepared as a raw material solution. The aqueous solution of a metal compound can be easily prepared, for example, by dissolving the metal compound in water having a temperature of about 30°C. The water is preferably pure water such as ion-exchanged water. The temperature of the aqueous solution of the metal compound is preferably about 30°C.

[0025] Examples of the metal compounds include metal sulfates, metal aluminates, and metal hydrates, but the present invention is not limited to these examples. These metal compounds may be used alone or in combination of two or more. Any of these compounds can be suitably used in the present invention.

[0026] The concentration of the metal compound in the aqueous solution of the metal compound is not particularly limited, but is usually 1.0 to 2.6 mol / L.

[0027] Next, the aqueous solution of the metal compound is added to water at 40 to 60°C, and the pH and ammonium ion (NH 4 + When the particles are crystallized, the formation of secondary particles due to the aggregation of primary particles proceeds in parallel.

[0028] The temperature of the water is preferably 40° C. or higher from the viewpoint of suppressing coarsening of the metal composite hydroxide particles, and is preferably 60° C. or lower from the viewpoint of suppressing miniaturization of the metal composite hydroxide particles. The water is preferably pure water such as ion-exchanged water.

[0029] It is preferable to use a reaction tank when adding the aqueous solution of the metal compound to water at 40 to 60° C. When a reaction tank is used, the aqueous solution of the metal compound is added to water at 40 to 60° C. injected into the reaction tank. The case where the reaction tank is used will be described below.

[0030] When the aqueous solution of the metal compound is added to water at 40 to 60° C., it is preferable to stir the water in order to efficiently crystallize the particles.

[0031] When crystallizing particles, in order to make the particles have a "solid" particle structure, it is preferable to introduce an inert gas such as nitrogen gas from the top of the reaction tank and adjust the atmosphere in the reaction tank to a non-oxidizing atmosphere with an oxygen concentration of 1 volume % or less.

[0032] In addition, when the particles are to have a "hollow" or "porous" particle structure, for example, the atmosphere in the reaction vessel is adjusted to an oxidizing atmosphere such as air, and the pH of the water in the reaction vessel is adjusted to 11.0 to 12.5 with a pH adjuster such as an aqueous sodium hydroxide solution, while the aqueous solution of the metal compound and ammonium ions (NH 4 + It is preferable to add aqueous ammonia to the reaction vessel in order to adjust the concentration of ammonium ions (NH 4 + ) is preferably 5 to 30 g / L, more preferably 10 to 20 g / L, from the viewpoint of stabilizing the crystallization treatment.

[0033] After the particles are crystallized, they are subsequently treated under the following conditions in order to have one of the following particle structures: "solid", "hollow" and "porous".

[0034] When the particles are to have a "solid" particle structure, for example, it is preferable to continue the crystallization treatment for growing the particles while maintaining the reaction tank in a non-oxidizing atmosphere. When the particles are to have a "hollow" particle structure, it is preferable to stop the addition of the aqueous solution of the metal compound and the ammonia water, change the atmosphere in the reaction tank from an oxidizing atmosphere to a non-oxidizing atmosphere, and then resume the addition of the aqueous solution of the metal compound and the ammonia water to continue the crystallization treatment for growing the particles. When the particles are to have a "porous" particle structure, for example, it is preferable to continue the crystallization treatment for growing the particles by performing a series of operations multiple times, such as stopping the addition of the aqueous solution of the metal compound and the ammonia water, changing the atmosphere in the reaction tank from an oxidizing atmosphere to a non-oxidizing atmosphere, resuming the addition of the aqueous solution of the metal compound and the ammonia water, changing the atmosphere from a non-oxidizing atmosphere to an oxidizing atmosphere, and changing the atmosphere from an oxidizing atmosphere to a non-oxidizing atmosphere.

[0035] As described above, by controlling the atmosphere in the reaction vessel to be a non-oxidizing atmosphere or an oxidizing atmosphere, the metal composite hydroxide can be adjusted to have a predetermined particle structure.

[0036] Here, by controlling the temperature in the reaction tank to 40 to 60°C, the particle size of the metal composite hydroxide can be adjusted to a preferred size. In addition, by controlling the pH of the water to 11.0 to 12.5, it is possible to reduce sulfates in the subsequent steps and adjust the particle size. In addition, ammonium ions (NH 4 + By controlling the concentration of the nitrile preferably to 5 to 30 g / L, more preferably to 10 to 20 g / L, the crystallization treatment can be stabilized.

[0037] By carrying out the above-mentioned operation, metal composite hydroxide (precursor) particles are obtained. From the viewpoint of improving the particle strength and increasing the contact area with the electrolyte, the porosity of the metal composite hydroxide particles is preferably 20% or less, more preferably 5% or less, when the metal composite hydroxide particles have a "solid" particle structure, preferably 10 to 90%, more preferably 20 to 50%, when the metal composite hydroxide particles have a "hollow" particle structure, and preferably 40 to 90%, more preferably 50 to 80%, when the metal composite hydroxide particles have a "porous" particle structure.

[0038] [Filtration / Drying] The crystallized product of the metal composite hydroxide particles obtained above is subjected to solid-liquid separation using a filtering device such as a filter press filter, and the recovered solid metal composite hydroxide particles are washed with washing water, whereby impurities can be removed from the metal composite hydroxide particles.

[0039] Since moisture is attached to the surface of the washed metal composite hydroxide particles, it is preferable to dry the metal composite hydroxide particles with a dryer. Examples of the dryer include a stationary dryer, a fluidized bed dryer, and an airflow dryer, but the present invention is not limited to these examples. When a heating dryer is used as the dryer, the heating dryer is preferably an electric heating dryer that does not generate carbon gas in a dry atmosphere.

[0040] The drying temperature for the metal composite hydroxide particles is preferably 100° C. or higher, more preferably 120° C. or higher, from the viewpoint of increasing the drying efficiency, and is preferably 200° C. or lower, more preferably 180° C. or lower, from the viewpoint of suppressing deterioration of the metal composite hydroxide particles. The drying time for the metal composite hydroxide particles differs depending on the drying temperature of the metal composite hydroxide particles and cannot be determined in general, so it is preferable to appropriately determine the drying temperature of the metal composite hydroxide particles and the like, but is usually about 1 to 5 hours.

[0041] The average particle size of the metal composite hydroxide particles is preferably 3 μm or more, more preferably 4 μm or more, from the viewpoint of increasing the packing density of the metal composite hydroxide particles to increase the battery capacity, and is preferably 20 μm or less, more preferably 15 μm or less, from the viewpoint of increasing the specific surface area of ​​the positive electrode active material and improving the output characteristics of the battery. The average particle size of the metal composite hydroxide particles is determined from a volume-based distribution measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Microtrack-Bell, product name: Microtrack MT3300EXII).

[0042] The composition of the metal composite hydroxide particles can be analyzed by a chemical analysis method such as acid decomposition-ICP (inductively coupled plasma) emission spectrometry.

[0043] (b) Preparation of metal composite oxide (intermediate) particles [Oxidation roasting] The metal composite hydroxide particles obtained above are oxidatively roasted in an oxygen-containing atmosphere such as air, whereby metal composite oxide particles, which are oxidatively roasted products, can be obtained.

[0044] When the metal composite hydroxide particles are oxidized and roasted, for example, a heating furnace such as a high-temperature heating furnace can be used. The heating furnace may be either a batch type heating furnace or a continuous type heating furnace. Among the heating furnaces, an electric furnace is preferred because there is no risk of generating combustion gas.

[0045] From the viewpoints of improving the mechanical strength of the metal composite oxide particles and preventing sintering of the metal composite oxide particles, the temperature at which the metal composite hydroxide particles are oxidatively roasted is preferably 800 to 1000° C., and more preferably 800 to 900° C. The time required for oxidatively roasting the metal composite hydroxide particles varies depending on the temperature at which the metal composite hydroxide particles are oxidatively roasted and cannot be determined in general, so it is preferable to appropriately determine the time depending on the temperature at which the metal composite hydroxide particles are oxidatively roasted, and is usually about 1 to 5 hours.

[0046] Before the oxidative roasting of the metal composite hydroxide particles, the metal composite hydroxide particles may be calcined in order to sufficiently remove moisture from the metal composite hydroxide particles and improve the mechanical strength of the metal composite hydroxide particles. The calcination of the metal composite hydroxide particles can be carried out, for example, by heating the metal composite hydroxide particles at a temperature of 400 to 550°C, preferably 450 to 500°C, for about 1 to 3 hours.

[0047] The average particle diameter of the metal composite oxide particles is preferably 3 μm or more, more preferably 4 μm or more, from the viewpoint of increasing the packing density of the metal composite oxide particles to increase the battery capacity, and is preferably 20 μm or less, more preferably 15 μm or less, from the viewpoint of increasing the specific surface area of ​​the positive electrode active material and improving the output characteristics of the battery. The average particle diameter of the metal composite oxide particles is determined from a volume-based distribution measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Microtrack-Bell Corporation, product name: Microtrack MT3300EXII).

[0048] The composition of the metal composite oxide particles can be analyzed by chemical analysis such as acid decomposition-ICP (inductively coupled plasma) emission spectrometry.

[0049] (c) Preparation of base powder As the raw material for the base powder, the metal composite oxide particles and the lithium compound particles are used.

[0050] [Lithium compound particles] The lithium compound constituting the lithium compound particles is, for example, lithium carbonate (Li 2 CO 3 , melting point: 723°C), lithium hydroxide (LiOH, melting point: 462°C), lithium nitrate (LiNO 3 , melting point: 261°C), lithium chloride (LiCl, melting point: 613°C), lithium sulfate (Li 2 SO 4, melting point: 859°C), but the present invention is not limited to these examples. These lithium compounds may be used alone or in combination of two or more. Among these lithium compounds, lithium hydroxide and lithium carbonate are preferred because they are easy to handle and have stable quality.

[0051] The maximum particle size of the lithium compound particles is preferably 10 μm or less, and the average particle size of the lithium compound particles is preferably 5 μm or less. The maximum particle size and the average particle size of the lithium compound particles are measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Microtrack Bell Co., Ltd., product name: Microtrack MT3300EXII), and the average particle size of the lithium compound particles is determined from the volume-based distribution measured using the measuring device.

[0052] [Preparation of lithium mixture] The metal composite oxide particles and lithium compound particles are mixed to obtain a lithium mixture.

[0053] The metal composite oxide particles and the lithium compound particles are preferably mixed so that the ratio value between the total number of atoms of the metal elements contained in the lithium metal composite oxide and the number of lithium atoms (hereinafter simply referred to as the "ratio value") is 1.0 to 1.2. The upper limit value of the ratio value is preferably 1.2 or less from the viewpoint of suppressing the coarsening of the particle size and the crystallite size and improving the cycle characteristics. When the metal composite oxide and the lithium compound are mixed at the ratio value, lithium atoms are taken into the 3a site, which is a lithium site, and therefore the battery characteristics can be improved. The site means a crystallographically equivalent lattice position. The presence of an atom at a lattice position is referred to as "the site is occupied", and the occupied site is referred to as "occupied site". LiCoO 2 For example, the LiCoO 2There are three occupied sites in the cation system, which are sometimes referred to as the lithium site, the cobalt site, and the oxygen site, or sometimes referred to as the 3a site, the 3b site, and the 6c site.

[0054] [Preparation of base powder] The lithium mixture is fired in an oxidizing atmosphere such as air to obtain a base powder containing secondary particles formed by aggregation of primary particles of the lithium metal composite oxide. The oxygen concentration in the oxidizing atmosphere is preferably 18 to 100% by volume.

[0055] The calcination temperature of the lithium mixture is preferably 800° C. or higher, more preferably 900° C. or higher, from the viewpoint of reducing the amount of unreacted lithium compounds and improving crystallinity, and is preferably 1000° C. or lower, from the viewpoint of suppressing excessive sintering between particles of the lithium metal composite oxide. The calcination time of the lithium mixture differs depending on the calcination temperature of the lithium mixture and cannot be determined in general, so it is preferable to appropriately determine the calcination time depending on the calcination temperature of the lithium mixture, and is usually preferably about 1 to 20 hours, more preferably about 10 to 15 hours.

[0056] Before firing the lithium mixture, the lithium mixture may be calcined in an oxygen-containing atmosphere such as air in order to improve the mechanical strength of the fired product by gently proceeding the reaction during firing of the lithium mixture and to reduce the amount of unreacted lithium compounds to improve crystallinity. The calcination of the lithium mixture can be carried out, for example, by heating the lithium mixture at a temperature of 400 to 550°C, preferably 450 to 500°C, for about 1 to 3 hours. The oxygen concentration in the oxygen-containing atmosphere is preferably 18 to 100% by volume.

[0057] By firing the lithium mixture in the above manner, primary particles of lithium metal composite oxide are formed from the metal composite oxide particles and the lithium compound particles, and a base powder containing secondary particles formed by aggregation of the primary particles of the lithium metal composite oxide is obtained. The secondary particles are usually spherical or elliptical, but may contain particles of an indefinite shape.

[0058] The particle size of the primary particles of the lithium metal composite oxide is not particularly limited, but is usually about 0.2 to 1 μm. The particle size of the secondary particles is usually about 3 to 30 μm. The particle sizes of the primary particles and the secondary particles are determined from a volume-based distribution measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Microtrack Bell Co., Ltd., product name: Microtrack MT3300EXII).

[0059] The base powder is essentially composed of the secondary particles, but may unavoidably contain a small amount of the primary particles in addition to the secondary particles.

[0060] In the present invention, the base material powder obtained above can be used as a raw material for the positive electrode active material for lithium ion secondary batteries, but commercially available base material powders may also be used. Among commercially available base material powders, those that use the base material powder to prepare a slurry having a predetermined pH can be used as the base material powder. The pH of the base material powder slurry will be described later.

[0061] Incidentally, the average thickness of the coating layer formed on the surface of the positive electrode active material of the present invention is very thin, at 3 to 150 nm, as described later, so that the positive electrode active material of the present invention inherits the powder characteristics and particle structure of the base powder, such as the average particle diameter MV, particle size distribution, and tap density (bulk density). Therefore, by selecting the powder characteristics and particle structure of the base powder, the properties of the base powder can be imparted to the positive electrode active material.

[0062] [Composition of lithium metal composite oxide] As described above, the base powder is substantially composed of the secondary particles, but may inevitably contain a small amount of the primary particles in addition to the secondary particles. Both the primary particles and the secondary particles are composed of a lithium metal composite oxide.

[0063] The lithium metal composite oxide is represented by the formula (I): Li s Ni 1-x-y Co x M y O 2+α (I) (In the formula, s, x, y and α are numbers satisfying 1.00≦s≦1.30, 0.05≦x≦0.35, 0≦y≦0.45 and −0.1≦α≦0.2, respectively, and M represents at least one metal element selected from the group consisting of Mn, V, Mg, Mo, Nb, Ti, W and Al.) It is preferable that the lithium metal composite oxide is represented by the following formula:

[0064] The composition of the base material powder can be determined, for example, by mixing appropriate amounts of the base material powder and inorganic acid (35% hydrochloric acid), decomposing the resulting mixture by heating, adding an appropriate amount of pure water to the resulting decomposition liquid to prepare an analytical specimen liquid, and subjecting the analytical specimen liquid to spectroscopic analysis using a multi-type ICP optical emission spectrometer (manufactured by Shimadzu Corporation, model number: ICPE-9000).

[0065] [pH of base powder slurry] Since the excess lithium compound contained in the base powder is mainly composed of lithium hydroxide, there is a strong correlation between the content of the excess lithium compound in the base powder and the pH of the base powder slurry. Therefore, by measuring the pH of the base powder slurry, the content of the excess lithium compound in the base powder can be determined more quickly and simply than by the conventional titration method.

[0066] The base material powder slurry can be prepared by mixing the base material powder and pure water at a ratio of 5 g of base material powder to 95 mL of pure water, and dispersing the base material powder in the pure water. The pH of the base material powder slurry is preferably 10.5 to 12.5, more preferably 11.0 to 12.5, even more preferably 11.0 to 12.2, and even more preferably 11.6 to 12.2, from the viewpoint of controlling the content of excess lithium compound contained in the base material powder to the optimal content of 0.045 to 1.6 mass %.

[0067] The pH of the base material powder slurry was measured by leaving the base material powder slurry undisturbed for 10 minutes and then measuring the pH of the supernatant liquid with a pH meter (manufactured by Thermo Fisher Scientific, Inc., trade name: Orion-star-A214 (tabletop type) or trade name: Orion-star-A221 (handheld type)).

[0068] [Average particle size MV and particle size distribution of base powder] The particle size distribution [(d90-d10) / average particle diameter MV], which is an index showing the spread of the particle size distribution of the base powder, is preferably 1.0 or less from the viewpoints of improving the filling property of the positive electrode active material and the battery capacity per battery volume, uniforming the applied voltage between the secondary particles constituting the positive electrode active material, and uniforming the load between the secondary particles to improve the cycle characteristics.

[0069] In the particle size distribution [(d90-d10) / average particle size MV], which is an index showing the spread of the particle size distribution, d10 means the particle size when the number of particles having each particle size is accumulated from the small particle size side and the accumulated volume is 10% of the total volume of all particles. Similarly to d10, d90 means the particle size when the number of particles having each particle size is accumulated from the small particle size side and the accumulated volume is 90% of the total volume of all particles.

[0070] The average particle size MV and particle size distribution [(d90-d10) / average particle size MV] of the base powder were determined from the volumetric distribution of the base powder measured using a laser diffraction / scattering type particle size distribution measuring device [Microtrack-Bell Corporation, product name: Microtrack MT3300EXII].

[0071] As with d10 and d90, the particle diameter where the cumulative volume is 50% of the total particle volume, in other words, the median diameter d50, may be used instead of the average particle diameter MV.

[0072] [Tap density (bulk density) of base powder] The tap density of the base powder is preferably 1.0 / cm from the viewpoint of reducing voids when an electrode for a lithium ion secondary battery is produced and improving battery performance. 3 More preferably, 1.8 / cm 3 More preferably, 2.0 / cm 3 The tap density of the base powder is preferably 3.0 / cm from the viewpoints of improving the contact area between the positive electrode active material and an electrolytic solution when the positive electrode active material is used in a non-aqueous electrolyte lithium ion secondary battery, and introducing a solid electrolyte between particles of the positive electrode active material when the positive electrode active material is used in an all-solid-state lithium ion secondary battery, thereby reducing the electrical resistance of the lithium ion secondary battery and increasing the battery capacity. 3 Less than or equal to 2.4 / cm 3 Less than 2.2 / cm, more preferably 3 The following is the result.

[0073] The tap density of the base powder is the density of the base powder measured after filling 12 g of the base powder into a 20 mL measuring cylinder, attaching the measuring cylinder to a shaking specific gravity measuring device (manufactured by Kuramochi Scientific Instruments Manufacturing Co., Ltd., product number: KRS-409), and allowing the measuring cylinder to freely fall from a height of 2 cm 500 times to densely pack the base powder.

[0074] (2) First mixture The first mixture can be obtained by mixing the base material powder and water so that the water content in the mixture of the base material powder and water is 4 to 7 mass %.

[0075] The water content in the mixture of base material powder and water is 4 mass% or more, preferably 5 mass% or more, from the viewpoint of allowing water to sufficiently penetrate into the gaps and grain boundaries between the primary particles that make up the secondary particles contained in the base material powder, and is 7 mass% or less, preferably 6 mass% or less, from the viewpoint of increasing the drying efficiency in the subsequent drying step, reducing the amount of lithium eluted from the base material powder, and improving the battery characteristics of a battery in which the positive electrode active material is used in the positive electrode.

[0076] The atmosphere and temperature when mixing the base material powder and water are not particularly limited. The atmosphere when mixing the base material powder and water may be air, or may be an inert gas such as nitrogen gas or argon gas. The temperature when mixing the base material powder and water can be appropriately determined usually from a temperature range of 5 to 95°C, preferably a temperature range of 10 to 80°C, but is usually preferably room temperature from the viewpoint of improving energy efficiency.

[0077] The base material powder and water can be mixed using a mixer such as a shaker mixer, a stirring mixer, a rocking mixer, etc. The base material powder and water are preferably mixed until both are uniformly dispersed and a mixture having a uniform composition is obtained.

[0078] (3) Second mixture The second mixture can be prepared by adjusting the temperature of the first mixture obtained above to 25 to 50° C. and mixing the first mixture with the coating raw material.

[0079] In the present invention, when the first mixture is mixed with the coating raw material, a coating raw material containing at least one compound selected from the group consisting of tungsten compounds and molybdenum compounds is used as the coating raw material, the total amount of tungsten and molybdenum contained in the coating raw material relative to the lithium of the excess lithium compound contained in the base material powder is adjusted to 0.8 to 1.2 equivalents, and the total amount of tungsten and molybdenum per 100 parts by mass of the base material powder is adjusted to 0.1 to 6 parts by mass.

[0080] In the present invention, since the above-mentioned operation is adopted, the lithium compound remaining on the surface of the base powder and the like can be dissolved, and the solubility of the added coating raw material in water can be improved, and as a result, a positive electrode active material for lithium ion secondary batteries can be obtained which has low positive electrode resistance and a high retention rate of discharge capacity when used in lithium ion secondary batteries.

[0081] As the coating raw material, a coating raw material containing at least one compound selected from the group consisting of tungsten compounds and molybdenum compounds is used. The tungsten compounds and molybdenum compounds may be used alone or in combination. Among the tungsten compounds and molybdenum compounds, the tungsten compounds are preferred because they are less likely to produce water as a by-product when reacting with excess lithium compounds.

[0082] Examples of tungsten compounds include tungsten oxide, tungstic acid, ammonium tungstate, etc., but the present invention is not limited to these examples. These tungsten compounds may be used alone, or two or more may be used in combination. Among tungsten compounds, tungsten oxide and tungstic acid are more preferred, and tungsten oxide is even more preferred, because they are less likely to produce water as a by-product when reacting with excess lithium compound.

[0083] Examples of molybdenum compounds include molybdenum oxide, molybdic acid, and ammonium molybdate, but the present invention is not limited to these examples. These molybdenum compounds may be used alone or in combination of two or more. Among the molybdenum compounds, molybdenum oxide and molybdic acid are preferred, and molybdenum oxide is more preferred, because they are less likely to produce water as a by-product when reacting with an excess lithium compound.

[0084] Tungsten oxide and molybdenum oxide are preferred from the viewpoints of improving the output characteristics of the lithium ion secondary battery and increasing the battery capacity. Among tungsten oxide and molybdenum oxide, tungsten oxide is preferred from the viewpoints of improving the lithium ion conductivity of the coating compound and promoting the movement of lithium ions.

[0085] The coating raw material may contain coating raw materials other than tungsten compounds and molybdenum compounds within the scope of the present invention. Examples of coating raw materials other than tungsten compounds and molybdenum compounds include vanadium pentoxide, niobium oxide, tin dioxide, manganese oxide, ruthenium oxide, rhenium oxide, tantalum oxide, phosphorus oxide, boron oxide, etc., but the present invention is not limited to these examples. These coating raw materials may be used alone or in combination of two or more types.

[0086] When an oxide such as tungsten oxide or molybdenum oxide or a hydrate of the oxide is used as the coating raw material, the coating raw material forms an oxoanion in the presence of water, and the oxoanion reacts with the lithium of the excess lithium compound to produce a lithium salt of the oxoanion such as lithium tungstate or lithium molybdate. When a positive electrode active material using the coating raw material is used in a lithium ion secondary battery, the positive electrode resistance of the lithium ion secondary battery can be reduced and the retention rate of the discharge capacity can be increased.

[0087] In addition, in the present invention, the total amount of tungsten and molybdenum contained in the coating raw material relative to the lithium of the excess lithium compound contained in the base material powder is 0.8 to 1.2 equivalents. Therefore, by using a positive electrode active material in which the coating raw material is used for a lithium ion secondary battery, the positive electrode resistance of the lithium ion secondary battery can be reduced and the retention rate of the discharge capacity can be increased.

[0088] When the total amount of tungsten and molybdenum contained in the coating raw material is small relative to the amount of excess lithium compound contained in the base material powder, the mixture of the first mixture and the coating raw material tends to gel, and when the total amount of tungsten and molybdenum is large relative to the amount of excess lithium compound contained in the base material powder, the crystal lattice of the base material powder constituting a composite oxide with nickel and cobalt, etc., is deprived of lithium necessary for intercalation and deintercalation, and the performance as a positive electrode active material tends to be not fully exhibited. Therefore, the total amount of tungsten and molybdenum contained in the coating raw material relative to the lithium of the excess lithium compound contained in the base material powder is 0.8 to 1.2 equivalents, preferably 0.9 to 1.1 equivalents, more preferably 0.95 to 1.05 equivalents, from the viewpoint of suppressing gelation of the mixture of the first mixture and the coating raw material and fully exhibiting the performance as a positive electrode active material.

[0089] The total amount of tungsten and molybdenum contained in the coating raw material relative to the lithium of the excess lithium compound contained in the base powder is 1 equivalent. For example, when the coating compound described later is dilithium ditungstate (Li 2 WO 4 ), it means the amount of reacting 2 moles of lithium atoms (atomic weight: 6.941) with 1 mole of tungsten atoms (atomic weight: 183.85), and the coating compound is dilithium dimolybdate (Li 2 MoO 4 ), it means the amount that reacts with 2 moles of lithium atoms (atomic weight: 6.941) and 1 mole of molybdenum atoms (atomic weight: 95.94). For example, pure lithium tungstate (Li 2WO 4 ) and lithium molybdate (Li 2 MoO 4 ), the composition ratio of lithium to tungsten (Li / W) and the composition ratio of lithium to molybdenum (Li / Mo) are both 2.

[0090] For example, as described above, the coating compound is Li 2 WO 4 and Li 2 MoO 4 In the case where the equivalent amount of the coating compound is a compound represented by formula (II): [Equivalent of coating compound] = [tungsten or molybdenum content (%) / atomic weight of tungsten or molybdenum] / [lithium content (%) / (atomic weight of lithium x 2)] (II) It is determined based on the following.

[0091] In addition, the coating compound is, for example, Li 4 WO 5 , Li 6 W 2 O 9 , Li 4 MoO 5 , Li 6 Mo 2 O 9 In the case of a compound such as above, the equivalent weight of the coating compound can be calculated by modifying formula (II) taking into account the moles of lithium atoms, tungsten atoms, and molybdenum atoms, respectively.

[0092] The total amount of tungsten and molybdenum contained in the coating raw material per 100 parts by mass of the base material powder is 0.1 to 6 parts by mass from the viewpoint of obtaining a positive electrode active material for a lithium ion secondary battery having low positive electrode resistance and high retention rate of discharge capacity when used in a lithium ion secondary battery.

[0093] The temperature of the first mixture when mixing the first mixture and the coating raw material is 25° C. or more, preferably 30° C. or more, and more preferably 33° C. or more, from the viewpoint of obtaining a positive electrode active material for lithium ion secondary batteries which has low positive electrode resistance and a high discharge capacity retention rate when used in lithium ion secondary batteries, and is 50° C. or less, preferably 45° C. or less, more preferably 40° C. or less, and even more preferably 37° C. or less, from the viewpoint of obtaining a positive electrode active material for lithium ion secondary batteries which has low positive electrode resistance and a high discharge capacity retention rate when used in lithium ion secondary batteries.

[0094] The atmosphere and temperature when mixing the first mixture and the coating raw material are not particularly limited. The atmosphere when mixing the first mixture and the coating raw material may be air, or may be an inert gas such as nitrogen gas or argon gas. The temperature when mixing the first mixture and the coating raw material can be appropriately determined preferably from the range of 5 to 95°C, more preferably from the range of 10 to 80°C, but is usually preferably room temperature.

[0095] The first mixture and the coating raw material can be mixed using a mixer such as a shaker mixer, a stirring mixer, a rocking mixer, etc. It is preferable that the first mixture and the coating raw material are mixed until both are uniformly dispersed and have a uniform composition.

[0096] (4) Positive electrode active material The positive electrode active material for lithium ion secondary batteries of the present invention is characterized in that a base powder containing secondary particles formed by agglomeration of primary particles of a lithium metal composite oxide containing lithium, nickel, and cobalt is used as a raw material, a coating layer containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate is formed on the surface of the secondary particles, the coating layer has an average thickness of 3 to 150 μm, and a coefficient of variation (CV%) indicating the variation in thickness of the coating layer is 15% or less. Since the positive electrode active material for lithium ion secondary batteries of the present invention has the above configuration, a lithium ion secondary battery having low positive electrode resistance and high retention rate of discharge capacity can be obtained by using the positive electrode active material.

[0097] The positive electrode active material can be prepared by drying the second mixture obtained above at a temperature of 150 to 250°C to form a coating layer on the surfaces of the secondary particles contained in the base powder.

[0098] The drying temperature for the second mixture is 150 to 250°C, preferably 160 to 240°C, and more preferably 170 to 230°C, from the viewpoints of efficiently drying the second mixture and forming a coating layer having a uniform thickness with little variation in thickness.

[0099] The drying of the second mixture is preferably carried out in an atmosphere of air from which carbon dioxide has been removed, nitrogen gas, argon gas, or other inert gas, from the viewpoint of avoiding a reaction between the carbon dioxide contained in the air and the coating layer. The pressure of the atmosphere when drying the second mixture is preferably reduced from atmospheric pressure, from the viewpoint of increasing the drying efficiency of the second mixture. The drying of the second mixture is preferably carried out until the weight loss of the second mixture is hardly observed. The drying time of the second mixture varies depending on the amount of the second mixture, the drying temperature, etc., and therefore cannot be determined in general, and is preferably determined appropriately depending on the amount of the second mixture, the drying temperature, etc., but is usually about 1 to 24 hours.

[0100] When drying the second mixture, for example, a dryer such as a stationary dryer, a vibration dryer, a drum dryer, or a spray dryer can be used.

[0101] In the present invention, the above-mentioned operation is adopted, and thus a positive electrode active material containing secondary particles having a coating layer with a preferred thickness on the surface of the base powder, with small variation in thickness, and containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate at a high content is obtained. In addition, since the secondary particles have a coating layer of lithium salt on their surfaces, the decrease in the specific surface area of ​​the positive electrode active material is suppressed, and the conduction path of lithium ions at the interface with the electrolyte and the solid electrolyte can be secured, so that the battery capacity of the lithium ion secondary battery can be increased and the positive electrode resistance can be reduced.

[0102] In this manner, a positive electrode active material containing secondary particles having, on the surface thereof, a coating layer containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate can be obtained.

[0103] When the coating compound constituting the coating layer contains excess lithium compounds such as lithium hydroxide as impurities, when a positive electrode composite paste for a non-aqueous electrolyte lithium ion secondary battery is prepared using a solvent, the lithium compounds dissolve in the solvent, and as the pH of the solvent increases, the concentration of the lithium salt in the solvent increases, which may cause gelation or the formation of a heterogeneous interface in an all-solid-state lithium ion secondary battery. In addition, when a positive electrode active material containing the lithium compounds is used for the positive electrode of a lithium ion secondary battery, the battery capacity and output characteristics are reduced. For these reasons, at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate, which have excellent resistance reducing functions, is used for the coating compound.

[0104] The average particle diameter MV of the positive electrode active material is preferably 5 to 15 μm from the viewpoints of improving the packing property of the positive electrode active material, improving the battery capacity per battery volume of the lithium ion secondary battery, equalizing the applied voltage between the secondary particles constituting the positive electrode active material, and equalizing the load between the secondary particles to improve the cycle characteristics. The average particle diameter MV of the positive electrode active material is determined from the volume-based distribution measured by a laser diffraction / scattering method.

[0105] The tap density (bulk density) of the positive electrode active material is 1.0 g / cm from the viewpoint of reducing voids when an electrode for a lithium ion secondary battery is produced and increasing the contact points between the positive electrode active material and the electrolyte and solid electrolyte to enhance battery performance. 3 It is preferable that the positive electrode active material has a density of 3.0 g / cm or more from the viewpoints of improving the contact area between the positive electrode active material and the electrolyte when the positive electrode active material is used in a non-aqueous electrolyte lithium ion secondary battery, and of sufficiently introducing a solid electrolyte between the particles of the positive electrode active material when the positive electrode active material is used in an all-solid-state lithium ion secondary battery, thereby reducing the electrical resistance of the lithium ion secondary battery and increasing the battery capacity. 3 It is preferable that:

[0106] When the positive electrode active material of the present invention is used as the positive electrode active material of a non-aqueous electrolyte lithium ion secondary battery, intercalation and deintercalation of lithium ions in the electrolyte and the positive electrode active material become active, and in an all-solid-state lithium ion secondary battery, lithium ions diffuse without stagnation at the interface between the solid electrolyte and the positive electrode active material, so that the positive electrode resistance can be reduced and the output characteristics can be improved while maintaining the durability of the lithium ion secondary battery.

[0107] In addition, when the secondary particles are aggregated, the secondary particles may be deflocculated as necessary using a deflocculating machine such as a pin mill, a hammer mill, a pulverizer, etc. In addition, the secondary particles may be deflocculated using a drum dryer that can simultaneously dry the second mixture and deflocculate the aggregated secondary particles.

[0108] When the coating layer formed on the surface of the secondary particles is lithium tungstate, the lithium tungstate may be, for example, Li 2 WO 4 , Li 4 WO 5 , Li 6 W 2 O 9 Or a mixture thereof. When the coating layer formed on the surface of the secondary particle is lithium molybdate, the lithium molybdate may be, for example, Li 2 MoO 4 , Li 4 MoO 5 , Li 6 Mo 2 O 9 Or a mixture of these.

[0109] The coating layer may contain lithium salts other than lithium tungstate and lithium molybdate within the scope of the present invention. Examples of lithium salts other than lithium tungstate and lithium molybdate include lithium vanadate, lithium niobate, lithium stannate, lithium manganate, lithium ruthenate, lithium rhenate, lithium tantalate, lithium phosphate, and lithium borate, but the present invention is not limited to these examples. These lithium salts may be used alone or in combination of two or more.

[0110] [Analysis of positive electrode active material] The positive electrode active material can be analyzed by the following method. (a) The content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) content The content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3The content of lithium hydroxide (LiOH) and lithium carbonate (Li) in the positive electrode active material is preferably less than 0.003 mass % from the viewpoint of obtaining a lithium ion secondary battery having low positive electrode resistance and high discharge capacity retention rate by using the positive electrode active material. 2 CO 3 The contents of each of the above are values ​​measured according to the following methods.

[0111] [Lithium hydroxide (LiOH) content and lithium carbonate (Li 2 CO 3 ) content measurement method The content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 The content of each of these can be determined by neutralization titration.

[0112] More specifically, lithium hydroxide and lithium carbonate present on the surface of the positive electrode active material particles dissolve in water and become hydroxide ions and carbonate ions, respectively, which are ionized from lithium ions. The ionized ions are titrated with an inorganic acid or the like to determine the amount of lithium hydroxide and lithium carbonate. The neutralization titration method is a sequential titration method based on the so-called RB Warder method. In the neutralization titration method, the first end point (pH: about 8.3) is the inflection point of pH when the entire amount of lithium hydroxide reacts with half of the lithium carbonate, and the second end point (pH: about 3.8) is the inflection point of pH when half of the remaining lithium carbonate reacts. The inflection point (end point) of pH can be confirmed by visually observing the color change of an indicator such as phenolphthalein or methyl orange, or by instrumentally reading the change in potential difference using a pH composite electrode.

[0113] More specifically, for example, 2 to 20 g of the positive electrode active material is taken, and the positive electrode active material is mixed with 120 mL of pure water. While stirring the resulting mixture, 1 mol / L of hydrochloric acid is gradually added to the mixture. Based on the two pH inflection points that appear, the content of lithium hydroxide (LiOH) and the content of lithium carbonate (Li 2 CO 3 The content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 When the content of each of the above compounds is to be determined, the content can be determined, for example, using an automatic titrator (manufactured by Hiranuma Sangyo Co., Ltd., product number: COM-1750) based on the end point (potential difference) measured by a pH composite electrode.

[0114] The content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 The lower the content of each of these, the more the boron contained in the coating raw material and the lithium in the lithium compound contained in the base powder reacted at a value close to 1 equivalent.

[0115] (b) pH of the positive electrode active material slurry The positive electrode active material slurry can be prepared by mixing the positive electrode active material and pure water in a ratio of 5 g of the positive electrode active material to 95 mL of pure water, and dispersing the positive electrode active material in the pure water. When the pH of the slurry is measured, it can be confirmed that no excess lithium compound remains by checking that the pH is 10 or less. The pH of the positive electrode active material slurry is a value measured according to the following method.

[0116] [Method for measuring pH of positive electrode active material slurry] The pH of the positive electrode active material slurry is determined by allowing the positive electrode active material slurry to stand for 10 minutes and then measuring the pH of the supernatant liquid with a pH meter (manufactured by Thermo Fisher Scientific, Inc., trade name: Orion-star-A214 (tabletop type)).

[0117] (c) Identification of the coating compound The coating compound constituting the coating layer present on the surface of the secondary particles used in the positive electrode active material can be identified by synchrotron radiation powder X-ray diffraction (SXRD) described later, but it is preferable to identify it by synchrotron radiation powder X-ray diffraction (SXRD) using "Spring-8" at the Synchrotron Radiation Research Center (RIKEN, National Research and Development Agency). The principles and phenomena of the synchrotron radiation powder X-ray diffraction (SXRD) are almost the same as those of general X-ray diffraction (XRD), and atomic arrangement and structure analysis can be performed based on information such as the wavelength of X-rays, the spacing between crystal planes, and the relationship between the angle between the crystal planes and the X-rays, based on Bragg's law.

[0118] By using synchrotron radiation powder X-ray diffraction method (SXRD), it is possible to analyze the type, structure, and properties of a trace substance in detail and accurately by taking advantage of the higher X-ray intensity and short pulse characteristics than X-ray diffraction method (XRD). Therefore, by using synchrotron radiation powder X-ray diffraction method (SXRD), it is possible to perform detailed structural analysis of a sample in which it is difficult to identify the target compound by X-ray diffraction method (XRD) due to high background noise. Therefore, synchrotron radiation powder X-ray diffraction method (SXRD) can be suitably used to confirm that the coating layer having a thickness of nanometers present on the surface of the secondary particles used in the positive electrode active material of the present invention is composed of a pure lithium salt.

[0119] (d) Average thickness and coefficient of variation CV% of the coating layer The average thickness of the coating layer formed on the surface of the secondary particles is 3 to 150 nm, preferably 4 to 120 nm, from the viewpoint of obtaining a positive electrode active material for a lithium ion secondary battery having low positive electrode resistance and high retention rate of discharge capacity when used in the lithium ion secondary battery. The average thickness of the coating layer is a value measured based on the following method.

[0120] The coefficient of variation CV% indicates the variation in the thickness of the coating layer. The coefficient of variation CV% is 15% or less from the viewpoint of stabilizing the intercalation and deintercalation of lithium ions and improving the lithium ion conductivity. The coefficient of variation CV% can be adjusted to 15% or less, for example, by controlling the thickness of the coating layer to a predetermined value. The coefficient of variation CV% is a value measured based on the following method.

[0121] [Method of measuring average thickness of coating layer and coefficient of variation CV%] When a positive electrode active material is observed using a transmission electron microscope (TEM), an image of the diffraction contrast (scattering contrast) of the interface between primary particles can be obtained, and therefore the TEM is mainly suitable for analyzing the crystallinity of the positive electrode active material. On the other hand, a scanning transmission electron microscope (STEM) is suitable for analyzing the composition of the layered structure in a compound and a semiconductor, since a HAADF-STEM (High-angle-Annular-Dark-Field-Scanning-TEM) image by Z (atomic number) contrast can be obtained using the scanning transmission electron microscope, such as confirmation of the layered structure in a compound and a semiconductor. Since a scanning transmission electron microscope (STEM) can obtain an image reflecting composition information, the thickness of the coating layer formed on the surface of the base material powder containing nickel and cobalt, such as the positive electrode active material of the present invention, can be accurately confirmed in nanometer units.

[0122] After drying the positive electrode active material, a cross-section polisher (CP) (manufactured by JEOL Ltd., product number: SM-09010) is used to process the secondary particles contained in the positive electrode active material to prepare a cross-sectional sample of the secondary particles, and the cross-section of the cross-sectional sample is observed with a scanning transmission electron microscope (STEM) (manufactured by JEOL Ltd., product number: ARM200F). Two straight lines that intersect at right angles at the approximate center of the observed image of the cross-section of the cross-sectional sample are drawn, and the thickness of the coating layer at four points that intersect with these two straight lines is measured, and the average thickness of the coating layer and the coefficient of variation CV%, which indicates the variation in the thickness of the coating layer, are calculated from the numerical values ​​of 10 secondary particles (n=40).

[0123] (e) Constituent elements of the coating compound (equivalent and composition ratio) In order to accurately specify the constituent elements and their morphology of the coating compound identified by synchrotron radiation powder X-ray diffraction (SXRD), it is preferable to conduct a chemical analysis in addition to an analysis of the physical properties of the coating compound.

[0124] The coating compound contains a water-soluble compound such as at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate. The water solubility of the coating compound can be utilized to analyze the constituent elements of the coating compound, and the total amount (equivalent weight) of tungsten and molybdenum can be determined based on formula (II). In addition, the type and form of each constituent element in the coating compound identified by synchrotron radiation powder X-ray diffraction (SXRD) can be confirmed to be appropriate by the following analysis method of the constituent elements of the coating compound.

[0125] [Method of Analyzing Constituent Elements of Coating Compound] A slurry was prepared by dispersing 5 g of the positive electrode active material in 95 mL of pure water at 25° C., and the slurry was stirred for 10 minutes and then filtered. Pure water was added to the filtrate so that the total volume was 200 mL to prepare an analysis specimen liquid. The analysis specimen liquid was appropriately diluted, and the contents of lithium, tungsten, and molybdenum contained in the analysis specimen liquid were measured using a multi-type ICP optical emission spectrometer (manufactured by Shimadzu Corporation, product number: ICPE-9000).

[0126] The composition ratio of lithium, tungsten, and molybdenum can be determined from the content of each element measured above and the total amount (equivalent) of tungsten and molybdenum determined based on formula (II), and it can be confirmed whether the composition ratio matches the coating compound identified by synchrotron radiation powder X-ray diffraction method (SXRD).

[0127] For example, as described in Example 1 below, tungsten oxide (WO 3) is adjusted to 0.23 g (tungsten (W) equivalent: 0.18 g), and tungsten oxide is added to the base powder as a coating raw material. When the lithium content in the entire cathode active material (dry material) contained in the coating compound (coating layer) present on the surface of the obtained cathode active material (dry material) is 0.014 mass% and the tungsten content in the coating compound (coating layer) is 0.20 mass% in the cathode active material (dry material), then 0.1 mmol (0.7 mg) of lithium and 0.05 mmol (10 mg) of tungsten are contained per 5 g of cathode active material, and the composition ratio of lithium to tungsten (lithium / tungsten) is 2.

[0128] In addition, for example, as described in Example 1 below, the coating compound identified by synchrotron radiation powder X-ray diffraction (SXRD) is dilithium ditungstate (Li 2 WO 4 ), the Li 2 WO 4 is composed of 2 moles of lithium, 1 mole of tungsten, and 4 moles of oxygen, so the composition ratio of lithium to tungsten (lithium / tungsten) is 2, which matches the composition ratio of lithium to tungsten (lithium / tungsten) of 2 determined by chemical analysis using a multi-type ICP atomic emission spectrometer (Shimadzu Corporation, model number: ICPE-9000).

[0129] In this way, whether the coating compound identified by synchrotron radiation powder X-ray diffraction (SXRD) is coated on the particle surface of the base powder can be evaluated by confirming that the analysis results by the physical analysis method and the analysis results by the chemical analysis method match. The reliability of the analysis results can be increased by performing both the physical analysis method and the chemical analysis method rather than performing only one of the two methods.

[0130] As shown in Comparative Example 9 below, 100 g of the base powder and dilithium ditungstate (Li 2 WO 4) is mixed with 1.04 g (tungsten equivalent: 0.73 g), when the lithium content in the positive electrode active material (dry material) is 0.13 mass% and the tungsten content is 0.73 mass%, the amount of lithium per 5 g of positive electrode active material is 0.9 mmol (6.5 mg) and the amount of tungsten is 0.2 mmol (36 mg), and the composition ratio of lithium to tungsten (ratio of the number of lithium / tungsten atoms) is 5.

[0131] However, the coating compound identified by synchrotron radiation powder X-ray diffraction (SXRD) was dilithium ditungstate (Li 2 WO 4 ), as described above, the composition ratio of lithium to tungsten (lithium / tungsten) should be 2. However, in Comparative Example 9, the composition ratio of lithium to tungsten determined by the ICP method, which is a chemical analysis method, is 5, which does not match. From this, it is concluded that the coating compound contains dilithium ditungstate (Li 2 WO 4 In addition to lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) is included.

[0132] (f) Lithium content in the base powder after preparation of the positive electrode active material When preparing a positive electrode active material, if the amount of coating raw material is greater than the amount of excess lithium compound present on the surfaces of the secondary particles of the base powder (if there is a shortage of lithium), as described above, lithium will be taken away by the base powder, and the resulting positive electrode active material may not fully exhibit its performance as a positive electrode active material.

[0133] The lithium salt constituting the coating layer of the positive electrode active material is insoluble in organic solvents and easily soluble in water. Therefore, the positive electrode active material is immersed in water, the coating layer is dissolved, and the base material powder is isolated, and the base material powder is completely dissolved with an inorganic acid or the like, so that an analytical sample liquid for measuring the lithium content contained in the base material powder can be prepared. More specifically, the lithium content in the base material powder can be measured by the following method.

[0134] [Method for measuring lithium content in base powder after preparation of positive electrode active material] A slurry is prepared by mixing 5 g of the positive electrode active material with 100 mL of pure water at room temperature, and the slurry is stirred for 10 minutes to dissolve the coating layer present on the surface of the base material powder in the water. The slurry is then filtered, and the resulting cake-like solid is collected.

[0135] The recovered solid content is added to an inorganic acid such as 35% hydrochloric acid, and decomposed by heating to a temperature of about 100 to 200°C. Pure water is added to the decomposition liquid so that the total volume of the resulting decomposition liquid becomes 200 mL, thereby preparing an analytical sample liquid.

[0136] The analytical sample liquid obtained above is appropriately diluted, and the amount of lithium in the analytical sample liquid is measured using a multi-type ICP optical emission spectrometer (Shimadzu Corporation, product number: ICPE-9000), whereby the lithium content in the base powder after preparation of the positive electrode active material can be determined.

[0137] As described above, according to the method for producing a positive electrode active material for a lithium ion secondary battery of the present invention, a coating compound constituting a coating layer having a resistance reducing function is coated on the particle surface of the base powder, the thickness of the coating layer is optimized, and a positive electrode active material for a lithium ion secondary battery in which the variation in the thickness of the coating layer (coefficient of variation CV%) is suppressed can be efficiently obtained.

[0138] Therefore, when the positive electrode active material for lithium ion secondary batteries of the present invention is used in a non-aqueous electrolyte lithium ion secondary battery, gelation during preparation of a positive electrode composite paste can be suppressed, thereby improving the quality and safety of the secondary battery. When the positive electrode active material is used in an all-solid-state lithium ion secondary battery, the formation of a heterogeneous interface is suppressed and the thickness of the coating layer becomes uniform and homogeneous, thereby improving the battery characteristics after preparation of the lithium ion secondary battery.

[0139] (g) Schematic diagram of a positive electrode active material for a lithium-ion secondary battery The positive electrode active material for lithium ion secondary batteries of the present invention will be described below with reference to Fig. 1. Fig. 1 is a schematic explanatory diagram showing one embodiment of the positive electrode active material for lithium ion secondary batteries of the present invention.

[0140] 1(a) shows a state in which primary particles 1 of a base powder are aggregated to form secondary particles 2. Since a coating layer having high lithium ion conductivity such as lithium tungstate and lithium molybdate is not formed on secondary particles 2 of the base powder, intercalation of lithium ions into the crystal lattice indicated by arrow A and deintercalation into the crystal lattice indicated by arrow B are not actively performed. Therefore, when secondary particles 2 are used in a lithium ion secondary battery, it is considered that the positive electrode resistance increases and the retention rate of discharge capacity decreases.

[0141] In contrast, in the positive electrode active material for a lithium ion secondary battery of the present invention, as shown in FIG. 1(b), primary particles 1 are aggregated to form secondary particles 2, and further a coating layer 3 is formed on the surface of the secondary particles 2. Therefore, due to the high lithium ion conductivity of the coating layer 3, intercalation of lithium ions into the crystal lattice indicated by arrow C and deintercalation into the crystal lattice indicated by arrow D are actively carried out. Therefore, when the secondary particles 2 are used in a lithium ion secondary battery, it is considered that the positive electrode resistance is reduced and the retention rate of the discharge capacity is improved.

[0142] 2. Lithium-ion secondary battery The lithium ion secondary battery of the present invention is characterized by having a positive electrode containing a positive electrode active material for lithium ion secondary batteries.

[0143] The components of the lithium ion secondary battery of the present invention are not particularly limited as long as they are the same as the components of lithium ion secondary batteries that are generally used. For example, when the lithium ion secondary battery of the present invention is a non-aqueous electrolyte lithium ion secondary battery, it includes a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. When the lithium ion secondary battery of the present invention is an all-solid-state lithium ion secondary battery, it includes a positive electrode, a negative electrode, and a solid electrolyte.

[0144] The embodiments of the lithium ion secondary battery of the present invention described below are merely examples, and embodiments in which various modifications or improvements have been made to the above embodiments based on the knowledge of those skilled in the art are included within the scope of the present invention.

[0145] (1) Non-aqueous electrolyte lithium-ion secondary battery [Positive electrode] First, the positive electrode active material of the present invention, a conductive material, and a binder are mixed to prepare a positive electrode mixture. Components such as activated carbon and an organic solvent used to adjust the viscosity are added to the positive electrode mixture as necessary, and the resulting mixture is further kneaded to obtain a positive electrode mixture paste.

[0146] The ratio of each component in the positive electrode mixture is an important factor in determining the performance of a lithium ion secondary battery. The ratio of each component in the positive electrode mixture is not particularly limited. The solid content of the positive electrode mixture from which the organic solvent has been removed preferably contains 60 to 95 mass % of a positive electrode active material, 1 to 20 mass % of a conductive material, and 1 to 20 mass % of a binder, similar to the positive electrode of a general lithium secondary battery.

[0147] Next, the positive electrode mixture paste is applied to the surface of a current collector made of, for example, aluminum foil, and then dried to volatilize and remove the organic solvent, thereby obtaining a positive electrode. If necessary, the positive electrode may be pressurized using a roll press or the like to increase the electrode density.

[0148] The positive electrode obtained in the manner described above is usually in the form of a sheet. The positive electrode is cut to an appropriate size as necessary and then used in the manufacture of a battery.

[0149] The present invention is not limited to the above-mentioned method for producing the positive electrode, and the positive electrode may be produced by other methods.

[0150] The conductive material may be, for example, graphite such as natural graphite, artificial graphite, or expanded graphite, or carbon black such as acetylene black or ketjen black. The binder may be, for example, fluorine-containing resin such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, ethylene-propylene-diene rubber, or fluorine rubber, styrene-butadiene rubber, cellulose-based resin, acrylic resin, polypropylene, or olefin-based resin such as polyethylene, which serves to bind the particles of the positive electrode active material.

[0151] In addition, after preparing a positive electrode mixture by mixing a positive electrode active material, a conductive material, and a binder, an organic solvent may be added to the positive electrode mixture to dissolve the binder, and the mixture may be kneaded to prepare a positive electrode mixture paste. For example, N-methyl-2-pyrrolidone (NMP) may be used as the organic solvent. Activated carbon may be added to the positive electrode mixture as necessary to increase the capacity of the electric double layer.

[0152] [Negative electrode] The negative electrode can be produced by mixing a negative electrode active material that absorbs and releases lithium metal, a lithium alloy, or lithium ions with a binder, adding an organic solvent to the resulting mixture to prepare a negative electrode mixture paste, applying the negative electrode mixture paste onto the surface of a current collector made of a metal foil such as copper foil, and drying the paste to volatilize and remove the organic solvent. If necessary, the negative electrode may be pressurized using a roll press or the like to increase the electrode density.

[0153] For example, natural graphite, artificial graphite, a calcined body of an organic compound such as phenolic resin, or a powder of a carbon material such as coke can be used as the negative electrode active material. As with the positive electrode, for example, a fluorine-containing resin-based binder such as polyvinylidene fluoride (PVDF) or a water-based binder such as styrene-butadiene rubber can be used as the negative electrode binder, as well as an organic solvent such as N-methyl-2-pyrrolidone (NMP) used to disperse the negative electrode active material and the binder. In addition, a viscosity modifier such as carboxymethyl cellulose (CMC) may be used in an appropriate amount in the negative electrode active material to improve the binding force.

[0154] [Separator] A separator is disposed between the positive electrode and the negative electrode. The separator is used to separate the positive electrode and the negative electrode and to hold the electrolyte. For example, a film made of a resin such as polyethylene or polypropylene with many fine through holes formed therein can be used as the separator.

[0155] [Non-aqueous electrolyte] The non-aqueous electrolyte is a solution in which a lithium salt as a supporting salt is dissolved in an organic solvent. Examples of the organic solvent include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and trifluoropropylene carbonate (TFPC); chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dipropyl carbonate (DPC); ether compounds such as tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), and dimethoxyethane (DME); sulfur compounds such as ethyl methyl sulfone and 1,4-butane sultone, and phosphate ester compounds such as triethyl phosphate and trioctyl phosphate, but the present invention is not limited to these examples. These organic solvents may be used alone or in combination of two or more.

[0156] The supporting salt is, for example, lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(trifluoromethanesulfonyl)imide [LiN(CF 3 SO 2 ) 2 ], their composite salts, etc., but the present invention is not limited to these examples. These supporting salts may be used alone or in combination of two or more kinds.

[0157] The non-aqueous electrolyte may contain additives such as a radical scavenger, a surfactant, and a flame retardant, as long as the object of the present invention is not impaired.

[0158] [Shape and configuration of lithium-ion secondary battery] The lithium ion secondary battery, which is composed of a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte solution, may have various shapes such as a cylindrical type, a laminated type, etc. Regardless of the shape of the lithium ion secondary battery, the positive electrode and the negative electrode are laminated with a separator interposed therebetween to form an electrode body, and the electrode body is impregnated with a non-aqueous electrolyte solution. A current collecting lead or the like is connected between the positive electrode and a positive electrode terminal connected to the outside, and between the negative electrode and a negative electrode terminal connected to the outside, respectively.

[0159] The electrode assembly having the above configuration is housed in a battery case and sealed, thereby completing a lithium ion secondary battery.

[0160] [Characteristics] A. Positive electrode resistance A 2032-type coin battery CBA is prepared, charged at a charging potential of 4.1 V, and measured by an AC impedance method using a frequency response analyzer and a potentiogalvanostat to obtain a Nyquist plot. This Nyquist plot is expressed as the sum of characteristic curves showing the solution resistance, the negative electrode resistance and its capacity, and the positive electrode resistance and its capacity, so that the positive electrode resistance can be calculated by performing fitting calculations using an equivalent circuit based on the Nyquist plot.

[0161] B. Initial discharge capacity and discharge capacity retention rate The initial discharge capacity was measured by leaving the 2032-type coin battery CBA for about 24 hours after production, and after the open-circuit voltage OCV (Open-Circuit-Voltage) had stabilized, applying a current density of 0.1 mA / cm to the positive electrode. 2 The discharge capacity is measured when the battery is charged to a cut-off voltage of 4.3 V, then after one hour of rest, discharged to a cut-off voltage of 3.0 V.

[0162] The discharge capacity retention rate was determined by holding the temperature of the coin battery CBA at 60° C., measuring the discharge capacity at the first cycle (initial discharge capacity), pausing for 10 minutes, and repeating the charge / discharge cycle for 500 cycles (charge / discharge), including the measurement of the initial discharge capacity, in the same manner as in the measurement of the initial discharge capacity, measuring the discharge capacity at the 500th cycle, and calculating the retention rate from the formula: [Discharge capacity retention rate (%)] = [(discharge capacity at 500th cycle) ÷ (initial discharge capacity)] × 100 This value was calculated based on the above.

[0163] (2) All-solid-state lithium-ion secondary battery [Positive electrode] The positive electrode contains positive electrode active material powder and Li 2 SP 2 S 5 Glasses containing Li 10 GeP 2 S 12 In one embodiment, a mixture obtained by mixing the sulfide-based lithium ion conductive solid electrolyte powder with a sulfide-based lithium ion conductive solid electrolyte powder such as 1,2-difluoromethane in an appropriate ratio (for example, 7:3 by mass) can be used.

[0164] [Negative electrode] For the negative electrode, a mixture obtained by mixing metallic lithium, a lithium-indium alloy, or a negative electrode active material capable of absorbing and desorbing lithium ions with a sulfide-based lithium ion conductive solid electrolyte powder in an appropriate ratio (for example, 7:3 by mass ratio) can be used. For the negative electrode active material, for example, natural graphite, artificial graphite, a fired body of an organic compound such as phenolic resin, or a powder of a carbon material such as coke can be used.

[0165] [Solid electrolyte] The solid electrolyte is, for example, a sulfide-based lithium ion conductive solid electrolyte having an ion conductivity of 10 -4 The lithium ion conductor preferably has a conductivity of 1.0 S / cm or more. Examples of the sulfide-based lithium ion conductive solid electrolyte include Li 2 SP 2 S 5 Glasses containing Li 10 GeP2 S 12 Glasses containing Li 3 PO 4 -Li 2 S-SiS 2 Glasses containing fluorine or the like may be mentioned, but the present invention is not limited to these examples.

[0166] [Shape and configuration of all-solid-state lithium-ion secondary battery] As described above, the all-solid-state lithium ion secondary battery has a positive electrode, a negative electrode, and a solid electrolyte. The shape of the all-solid-state lithium ion secondary battery can be, for example, a circular type or a sheet type. Regardless of the shape of the all-solid-state lithium ion secondary battery, the positive electrode and the negative electrode are used as electrode bodies, a solid electrolyte is present between the positive electrode and the negative electrode, and a positive electrode current collector provided on the positive electrode and a positive electrode terminal connected to the outside, and a negative electrode current collector provided on the negative electrode and a negative electrode terminal connected to the outside are connected by current collecting leads or the like, and these are housed in a battery case and sealed to obtain an all-solid-state lithium ion secondary battery.

[0167] [Characteristics] A. Positive electrode resistance The positive electrode resistance is the value obtained by charging the all-solid-state battery to a charging potential of 4.0 V, measuring the AC impedance using a frequency response analyzer and a potentiogalvanostat, and calculating the positive electrode resistance from the obtained impedance spectrum using an equivalent circuit.

[0168] B. Initial discharge capacity and discharge capacity retention rate The initial discharge capacity is the capacity when the all-solid-state battery is produced, charged to a charging potential of 4.2 V at a constant current density, and discharged to 3.0 V. The retention rate of the discharge capacity is measured by holding the all-solid-state battery at 25° C. and measuring the initial discharge capacity, and then repeating the charge / discharge cycle 50 times (charge / discharge) including the measurement of the initial discharge capacity in the same manner as in the measurement of the initial discharge capacity, measuring the discharge capacity at the 50th cycle, and calculating the retention rate from the formula: [Discharge capacity retention rate (%)] = [(50th cycle discharge capacity) ÷ (initial discharge capacity)] × 100 This value was calculated based on the above. EXAMPLES

[0169] Next, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.

[0170] In each example, the base material powder, the positive electrode active material, and the reagents used in manufacturing the lithium ion secondary battery were all special grade reagents manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The base material powder and the positive electrode active material were analyzed and identified, and the results are shown in Table 1. and Table 2 As shown in.

[0171] [Example 1] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.6 g / cm 3 The powder of lithium metal composite oxide having a base powder slurry pH of 11.0 was used.

[0172] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0173] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the coating compound to be produced was 1 equivalent relative to the amount of excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0174] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0175] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0176] The average thickness of the coating layer of the positive electrode active material was 4 nm, and the coefficient of variation CV% indicating the variation in thickness was 15%. In addition, the pH of the slurry of the positive electrode active material was 9.5, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0177] The lithium content in the base material powder after preparation of the positive electrode active material (shown in the "Li in base material powder" column in Table 1) was 7.1 mass %.

[0178] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.27. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 90%.

[0179] The positive electrode resistance value and the discharge capacity retention rate of the lithium ion secondary battery were measured based on the following methods.

[0180] [Method of measuring positive electrode resistance value and discharge capacity retention rate] Positive electrode active material and 75Li 2 S-25P 2 S 5The negative electrode was made of 15 mg of a mixture of 75Li and glass in a mass ratio of 7:3. 2 S-25P 2 S 5 The solid electrolyte was 75Li. 2 S-25P 2 S 5 150 mg of glass was used.

[0181] The positive electrode, the solid electrolyte, and the negative electrode were stacked to prepare a three-layer laminate, and the obtained laminate was press-molded to a diameter of 10 mm at a pressure of 300 MPa. Stainless steel plates were press-bonded to both sides of the obtained molded body to form current collectors, thereby preparing a circular all-solid-state lithium ion secondary battery.

[0182] (1) Positive electrode resistance value The all-solid-state lithium-ion secondary battery obtained above was charged at a charging potential of 4.0 V, and an impedance spectrum was obtained by measuring with an AC impedance method using a frequency response analyzer and a potentiogalvanostat 1255B (manufactured by Solartron, UK, product name). Two semicircles were observed in the high frequency region and the intermediate frequency region in the impedance spectrum obtained above, and the positive electrode resistance value was calculated by analyzing the semicircle in the intermediate frequency region using an equivalent circuit.

[0183] (2) Discharge capacity retention rate The all-solid-state lithium-ion secondary battery obtained above is charged at a constant current density in air at 25° C. until the potential reaches 4.2 V, and then discharged until the potential reaches 3.0 V, and the initial discharge capacity is measured.

[0184] After measuring the initial discharge capacity, charge and discharge were repeated 50 cycles including the measurement of the initial discharge capacity in the same manner as in the measurement of the initial discharge capacity, and then the discharge capacity at the 50th cycle was measured to obtain the formula (III): [Discharge capacity retention rate (%)] = {[Discharge capacity at a given point in time (mAh or Ah)] ÷[Initial discharge capacity (mAh or Ah)]} × 100 (III) The discharge capacity retention rate was calculated based on the above.

[0185] [Example 2] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.6 g / cm 3 The powder of lithium metal composite oxide having a base powder slurry pH of 11.3 was used.

[0186] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0187] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the coating compound to be produced was 1 equivalent relative to the amount of excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0188] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0189] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO4 ) was confirmed.

[0190] The average thickness of the coating layer of the positive electrode active material was 7 nm, and the coefficient of variation CV% indicating the variation in thickness was 12%. In addition, the pH of the slurry of the positive electrode active material was 9.7, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0191] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.24. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 91%.

[0192] [Example 3] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.7 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.7 g / cm 3 The powder of lithium metal composite oxide having a base powder slurry pH of 11.6 was used.

[0193] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0194] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0195] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0196] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0197] The average thickness of the coating layer of the positive electrode active material was 14 nm, and the coefficient of variation CV% indicating the variation in thickness was 8.6%. In addition, the pH of the slurry of the positive electrode active material was 9.7, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0198] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.18. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 92%.

[0199] [Example 4] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.6 g / cm 3 The powder of lithium metal composite oxide having a base powder slurry pH of 11.9 was used.

[0200] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0201] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0202] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0203] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0204] The average thickness of the coating layer of the positive electrode active material was 29 nm, and the coefficient of variation CV% indicating the variation in thickness was 5.2%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3) was confirmed to be less than 0.003 mass% in each case.

[0205] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.11. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 93%.

[0206] [Example 5] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.80, and the tap density is 2.6 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 12.2.

[0207] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0208] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0209] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0210] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0211] The average thickness of the coating layer of the positive electrode active material was 57 nm, and the coefficient of variation CV% indicating the variation in thickness was 3.4%. In addition, the pH of the slurry of the positive electrode active material was 9.5, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0212] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.15. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 92%.

[0213] [Example 6] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.7 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.7 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 12.5.

[0214] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0215] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0216] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0217] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0218] The average thickness of the coating layer of the positive electrode active material was 116 nm, and the coefficient of variation CV% indicating the variation in thickness was 5.1%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0219] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.22. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 90%.

[0220] [Example 7] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.0 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 11.5.

[0221] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0222] Molybdenum trioxide (MoO 3 The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with molybdenum trioxide (MoO 3 ) to obtain a second mixture.

[0223] Next, the second mixture obtained above was dried at a temperature of 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0224] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0225] The average thickness of the coating layer of the positive electrode active material was 10 nm, and the coefficient of variation CV% indicating the variation in thickness was 11%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0226] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.20. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 90%.

[0227] [Example 8] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.1 μm, the particle size distribution [(d90-d10) / average particle size] is 0.80, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide having a base powder slurry pH of 12.0 was used.

[0228] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0229] Molybdenum trioxide (MoO 3The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with molybdenum trioxide (MoO 3 ) to obtain a second mixture.

[0230] Next, the second mixture obtained above was dried at a temperature of 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0231] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0232] The average thickness of the coating layer of the positive electrode active material was 33 nm, and the coefficient of variation CV% indicating the variation in thickness was 6.2%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0233] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.13. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 93%.

[0234] [Example 9] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.1 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide having a base powder slurry pH of 12.4 was used.

[0235] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0236] Molybdenum trioxide (MoO 3 The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with molybdenum trioxide (MoO 3 ) to obtain a second mixture.

[0237] Next, the second mixture obtained above was dried at a temperature of 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0238] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0239] The average thickness of the coating layer of the positive electrode active material was 82 nm, and the coefficient of variation CV% indicating the variation in thickness was 4.3%. In addition, the pH of the slurry of the positive electrode active material was 9.5, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0240] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.19. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 91%.

[0241] [Example 10] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.9 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 12.1.

[0242] The lithium metal composite oxide powder (100 g) and water (6 g) were mixed together to obtain a first mixture.

[0243] Tungsten trioxide (WO 3 ) and molybdenum trioxide (MoO 3) in a molar ratio of 1:1 to obtain a coating raw material mixture. The total amount of tungsten and molybdenum contained in the coating compound to be produced was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1 per 100 g of the lithium metal composite oxide powder so that the total amount of tungsten and molybdenum contained in the coating raw material mixture was 1 equivalent to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. The first mixture and the coating raw material mixture were mixed while adjusting the temperature of the first mixture obtained above to 35°C to obtain a second mixture.

[0244] Next, the second mixture obtained above was dried at a temperature of 200° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0245] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found that the coating compound was lithium tungstate and lithium molybdate, and that the composition was dilithium ditungstate (Li 2 WO 4 ) and dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0246] The average thickness of the coating layer of the positive electrode active material was 45 nm, and the coefficient of variation CV% indicating the variation in thickness was 4.4%. In addition, the pH of the slurry of the positive electrode active material was 9.7, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0247] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.16. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 92%. The positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.16, where the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) was taken as 1.00, and it was confirmed that the discharge capacity retention rate of the lithium ion secondary battery was 92%.

[0248] [Comparative Example 1] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.80, and the tap density is 2.6 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 10.5.

[0249] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0250] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3) to obtain a second mixture.

[0251] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0252] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0253] The average thickness of the coating layer of the positive electrode active material was 1 nm, and the coefficient of variation CV% indicating the variation in thickness was 82%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0254] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.58. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 85%.

[0255] [Comparative Example 2] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.7 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.6 g / cm 3 The lithium metal composite oxide powder used had a base powder slurry pH of 13.0.

[0256] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0257] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0258] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0259] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0260] The average thickness of the coating layer of the positive electrode active material was 360 nm, and the coefficient of variation CV% indicating the variation in thickness was 18%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0261] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.40. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 86%.

[0262] [Comparative Example 3] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.0 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 10.8.

[0263] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0264] Molybdenum trioxide (MoO 3 The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the coating compound to be produced was 1 equivalent relative to the amount of excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with molybdenum trioxide (MoO 3 ) to obtain a second mixture.

[0265] Next, the second mixture obtained above was dried at a temperature of 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0266] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0267] The average thickness of the coating layer of the positive electrode active material was 2 nm, and the coefficient of variation CV% indicating the variation in thickness was 53%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0268] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.61. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 85%.

[0269] [Comparative Example 4] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.1 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide was used, in which the pH of the base powder slurry was 12.8.

[0270] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0271] Molybdenum trioxide (MoO 3The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with molybdenum trioxide (MoO 3 ) to obtain a second mixture.

[0272] Next, the second mixture obtained above was dried at a temperature of 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0273] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0274] The average thickness of the positive electrode active material was 206 nm, and the coefficient of variation CV% indicating the variation in thickness was 19%. In addition, the pH of the slurry of the positive electrode active material was 9.7, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0275] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.44. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 86%.

[0276] [Comparative Example 5] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.6 g / cm 3 A lithium metal composite oxide having a base powder slurry pH of 11.8 was used.

[0277] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0278] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total amount of W and Mo" column in Table 1, and the first mixture and tungsten trioxide (WO 3 ) at room temperature to obtain a second mixture.

[0279] Next, the second mixture obtained above was dried at a temperature of 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0280] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0281] The average thickness of the positive electrode active material was 23 nm, and the coefficient of variation CV% indicating the variation in thickness was 17%. In addition, the pH of the slurry of the positive electrode active material was 9.5, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0282] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.32. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 87%.

[0283] [Comparative Example 6] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.0 μm, the particle size distribution [(d90-d10) / average particle size] is 0.80, and the tap density is 2.5 g / cm 3 A lithium metal composite oxide having a base powder slurry pH of 11.7 was used.

[0284] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0285] Molybdenum trioxide (MoO 3 The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total amount of W and Mo" column in Table 1, and the first mixture and molybdenum trioxide (MoO3 ) at room temperature to obtain a second mixture.

[0286] Next, the second mixture obtained above was dried at 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0287] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0288] The average thickness of the positive electrode active material was 16 nm, and the coefficient of variation CV% indicating the variation in thickness was 16%. In addition, the pH of the slurry of the positive electrode active material was 9.5, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0289] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.38. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 87%.

[0290] [Comparative Example 7] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.8 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.6 g / cm 3 A lithium metal composite oxide having a base powder slurry pH of 12.1 was used.

[0291] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total amount of W and Mo" column in Table 1, and the first mixture and tungsten trioxide (WO 3 ) at room temperature to obtain mixture A.

[0292] Next, 100 g of the mixture A obtained above was mixed with 7 g of water to obtain a mixture B. The obtained mixture B was dried at 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0293] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0294] The average thickness of the positive electrode active material was 45 nm, and the coefficient of variation CV% indicating the variation in thickness was 23%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0295] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.65. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 85%.

[0296] [Comparative Example 8] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 12.0 μm, the particle size distribution [(d90-d10) / average particle size] is 0.82, and the tap density is 2.5 g / cm 3 The lithium metal composite oxide used had a slurry pH of 12.2.

[0297] Molybdenum trioxide (MoO 3 The amount of molybdenum trioxide (MoO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total amount of W and Mo" column in Table 1, and the first mixture and molybdenum trioxide (MoO 3 ) at room temperature to obtain mixture A.

[0298] Next, 100 g of the mixture A obtained above was mixed with 4 g of water to obtain a mixture B. The obtained mixture B was dried at 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0299] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium molybdate, with a composition of dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0300] The average thickness of the positive electrode active material was 51 nm, and the coefficient of variation CV% indicating the variation in thickness was 33%. In addition, the pH of the slurry of the positive electrode active material was 9.6, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0301] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.77. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 85%.

[0302] [Comparative Example 9] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 The average particle size MV is 11.7 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.6 g / cm 3 The lithium metal composite oxide used had a slurry pH of 11.6.

[0303] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0304] Dilithium ditungstate (Li 2 WO 4 The amount of dilithium ditungstate (Li ) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 2 WO 4The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with dilithium ditungstate (Li 2 WO 4 ) to obtain a second mixture.

[0305] Next, the second mixture obtained above was dried at 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0306] The coating compound on the particle surface of the positive electrode active material obtained above was identified. In addition to identifying lithium tungstate as the coating compound, lithium hydroxide and lithium carbonate (Li 2 CO 3 ) was detected, and the composition of lithium tungstate was found to be dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0307] The average thickness of the positive electrode active material was 21 nm, and the coefficient of variation CV% indicating the variation in thickness was 22%. In addition, the pH of the slurry of the positive electrode active material was 11.2, the content of lithium hydroxide in the positive electrode active material was 0.076 mass%, and the content of lithium carbonate (Li 2 CO 3 ) was confirmed to be 0.006 mass%.

[0308] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.84. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 83%.

[0309] [Comparative Example 10] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co0.15 Al 0.03 O 2 The average particle size MV is 12.0 μm, the particle size distribution [(d90-d10) / average particle size] is 0.81, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide having a slurry pH of 11.5 was used.

[0310] The lithium metal composite oxide powder (100 g) and water (4 g) were mixed together to obtain a first mixture.

[0311] Dilithium dimolybdate (Li 2 MoO 4 The amount of dilithium dimolybdate (Li) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of molybdenum contained in the resulting coating compound was 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 2 MoO 4 The amount of molybdenum contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with dilithium dimolybdate (Li 2 MoO 4 ) to obtain a second mixture.

[0312] Next, the second mixture obtained above was dried at 170° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0313] Identification of the coating compound on the particle surface of the positive electrode active material obtained above revealed that in addition to lithium molybdate, lithium hydroxide and lithium carbonate (Li 2 CO 3 ) was detected, and the composition of lithium molybdate was found to be dilithium dimolybdate (Li 2 MoO 4 ) was confirmed.

[0314] The average thickness of the positive electrode active material was 15 nm, and the coefficient of variation CV% indicating the variation in thickness was 26%. In addition, the pH of the slurry of the positive electrode active material was 11.3, the content of lithium hydroxide in the positive electrode active material was 0.096 mass%, and the content of lithium carbonate (Li 2 CO 3 ) was confirmed to be 0.008 mass%.

[0315] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.89. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 82%.

[0316] [Comparative Example 11] As the base powder, the same lithium metal composite oxide powder as that used in Example 6 was used.

[0317] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0318] Tungsten trioxide (WO 3 The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was significantly less than 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0319] Next, the second mixture obtained above was dried at 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0320] Identification of the coating compound on the particle surface of the positive electrode active material obtained above revealed that in addition to lithium tungstate, lithium hydroxide and lithium carbonate (Li 2 CO 3 ) was detected, and the composition of lithium tungstate was found to be dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0321] The average thickness of the positive electrode active material was 54 nm, and the coefficient of variation CV% indicating the variation in thickness was 23%. In addition, the pH of the slurry of the positive electrode active material was 12.3, the content of lithium hydroxide in the positive electrode active material was 0.95 mass%, and the content of lithium carbonate (Li 2 CO 3 ) was confirmed to be 0.065 mass%.

[0322] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.96. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 74%.

[0323] [Comparative Example 12] As the base powder, the same lithium metal composite oxide powder as that used in Example 1 was used.

[0324] The lithium metal composite oxide powder (100 g) and water (7 g) were mixed together to obtain a first mixture.

[0325] Tungsten trioxide (WO 3The amount of tungsten trioxide (WO) per 100 g of the lithium metal composite oxide powder was adjusted so that the amount of tungsten contained in the resulting coating compound was significantly in excess of 1 equivalent relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide powder. 3 The amount of tungsten contained in the first mixture was adjusted to the amount shown in the "Total Amount of W and Mo" column in Table 1, and the first mixture was mixed with tungsten trioxide (WO) while adjusting the temperature of the first mixture to 40°C. 3 ) to obtain a second mixture.

[0326] Next, the second mixture obtained above was dried at 230° C. for 12 hours, and then some of the aggregates were deflocculated using a deflocculator to obtain a positive electrode active material.

[0327] The coating compound on the particle surface of the positive electrode active material obtained above was identified, and it was found to be lithium tungstate, and its composition was dilithium ditungstate (Li 2 WO 4 ) was confirmed.

[0328] The average thickness of the positive electrode active material was 36 nm, and the coefficient of variation CV% indicating the variation in thickness was 17%. In addition, the pH of the slurry of the positive electrode active material was 9.5, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was confirmed to be less than 0.003 mass% in each case.

[0329] The lithium content in the base powder after preparation of the positive electrode active material was 6.9 mass %.

[0330] When the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained in Comparative Example 13 (without coating) described later was taken as 1.00, the positive electrode resistance value of the lithium ion secondary battery produced using the positive electrode active material obtained above was 0.91. In addition, the retention rate of the discharge capacity of the lithium ion secondary battery obtained above was 78%.

[0331] [Comparative Example 13] The base powder has a solid particle structure and a Li 1.02 Ni 0.82 Co 0.15 Al 0.03 O 2 , the average particle diameter MV is 11.9 μm, the particle size distribution [(d90-d10) / average particle diameter] is 0.82, and the tap density is 2.5 g / cm 3 The powder of lithium metal composite oxide having a slurry pH of 12.1 was used.

[0332] The lithium metal composite oxide was not coated with any of the above-mentioned lithium metal composite oxides, and the lithium ion secondary battery was evaluated for its characteristics using the lithium metal composite oxides as a positive electrode active material. As a result, the positive electrode resistance value of the lithium ion secondary battery was 1.00, and the retention rate of the discharge capacity was 67%.

[0333] [Table 1] [Table 2]

[0334] [comprehensive evaluation] table 2 From the results shown in Fig. 1, it can be seen that the positive electrode active material obtained in each Example has an average thickness of the coating layer within the range of 3 to 150 nm, and the coefficient of variation (CV%) indicating the variation in thickness is 15% or less. In addition, the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3It can be seen that the content of tungsten and molybdenum in the coating compound produced is 0.8 to 1.2 equivalents in total relative to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide in each of the positive electrode active materials obtained in the Examples.

[0335] In addition, the physical analysis method, synchrotron radiation powder X-ray diffraction (SXRD), revealed that the coating compound was dilithium ditungstate (Li 2 WO 4 ), dilithium dimolybdate (Li 2 MoO 4 ), or a mixture thereof. SXRD The composition ratios of lithium, tungsten, and molybdenum [lithium / tungsten, lithium / molybdenum, or lithium / (tungsten + molybdenum)] based on the identification results of SXRD match with the composition ratio of lithium [lithium / tungsten, lithium / molybdenum, or lithium / (tungsten + molybdenum)] determined in parallel based on the respective contents of lithium, tungsten, and molybdenum by chemical analysis, indicating that the coating compound formed is as identified by the synchrotron radiation powder X-ray diffraction (SXRD) method.

[0336] From the above results, it can be seen that in each Example, a positive electrode active material for a lithium ion secondary battery was obtained in which the particle surface of the base powder was purely coated with a coating compound having a resistance reducing function in an approximately equivalent amount, the thickness of the coating layer was optimized, and the variation in the thickness of the coating layer was minimized.

[0337] Therefore, it can be seen that the positive electrode resistance values ​​of the lithium ion secondary batteries fabricated using the positive electrode active materials obtained in each Example were all less than 0.30, and the discharge capacity retention rates were all 90% or more, which are very excellent results.

[0338] In contrast, the positive electrode active materials obtained in each comparative example, including those without a coating layer, had average coating layer thicknesses and coefficients of variation (CV%) indicating thickness variations that were both outside the optimal range, indicating that the battery characteristics were inferior.

[0339] In Comparative Examples 9 and 10, the coating compound dilithium ditungstate (Li 2 WO 4 ) or dilithium dimolybdate (Li 2 MoO 4 ) is used as is, the excess lithium in the lithium compound contained in the base powder is mixed into the coating layer as an impurity in an unreacted state, and lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) was identified, and it was found that the pH of the slurry of the positive electrode active material exceeded 11. This indicates that the content of lithium hydroxide was high, and the total amount of tungsten and molybdenum contained in the coating compound was not equivalent to the amount of lithium in the excess lithium compound contained in the lithium metal composite oxide. This tendency is also observed when the amount of coating raw material is insufficient relative to the amount of lithium in the excess lithium compound contained in the base powder, as in the positive electrode active material obtained in Comparative Example 11.

[0340] On the other hand, in the positive electrode active material obtained in Comparative Example 12, the coating raw material tungsten trioxide (WO 3 The amount of tungsten trioxide (WO 3 ) may remain, but dilithium ditungstate (Li 2 WO 4 ) was identified as pure, and the content of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 ) is less than 0.003 mass %, and the amount of the coating compound is within the range of 0.8 to 1.2 equivalents.

[0341] However, the lithium content in the base powder of the positive electrode active material obtained in Comparative Example 12 was 6.9 mass%, while the lithium content in the positive electrode active material obtained in Example 1 was 7.1 mass%. This shows that, in the positive electrode active material obtained in Comparative Example 12, lithium is removed not only from nickel and cobalt but also from the base powder itself constituting the composite oxide.

[0342] In addition, since the positive electrode resistance value and the retention rate of discharge capacity of the lithium ion secondary battery are inferior in the positive electrode active material obtained in Comparative Example 12 to those in the positive electrode active material obtained in Example 1, it is considered that the battery characteristics of the positive electrode active material obtained in Comparative Example 12 are deteriorated because lithium is taken from the base powder itself by an excessive amount of coating raw material.

[0343] As described above, the positive electrode active material for lithium ion secondary batteries of the present invention has low positive electrode resistance and high retention rate of discharge capacity when used in lithium ion secondary batteries, and therefore can be suitably used in lithium ion secondary batteries. [Explanation of symbols]

[0344] 1 primary particle 2 Secondary particles 3 Covering layer

Claims

[Claim 1] A method for producing a positive electrode active material for a lithium ion secondary battery using a base powder containing secondary particles formed by agglomeration of primary particles of a lithium metal composite oxide containing lithium, nickel, and cobalt as a raw material, comprising the steps of: The lithium metal composite oxide has the formula (I): Li s Ni 1-xy C x M y O 2+α (I) (In the formula, s, x, y, and α are numbers satisfying 1.00≦s≦1.30, 0.05≦x≦0.35, 0≦y≦0.45, and −0.1≦α≦0.2, respectively, and M represents Al.) a coating layer containing at least one lithium salt selected from the group consisting of lithium tungstate and lithium molybdate is formed on a surface of the secondary particles, the coating layer has an average thickness of 3 to 150 nm, and a coefficient of variation (CV%) indicating the variation in thickness of the coating layer is 15% or less; preparing a first mixture by mixing the base material powder and water such that the water content in the mixture of the base material powder and water is 4 to 7 mass %; The temperature of the first mixture obtained above is adjusted to 25 to 50°C, and the first mixture is mixed with a coating material to prepare a second mixture; The second mixture is dried at a temperature of 150 to 250° C. to form a coating layer on the surface of the secondary particles contained in the base powder, thereby producing a positive electrode active material; A coating raw material containing at least one compound selected from the group consisting of tungsten compounds and molybdenum compounds is used as the coating raw material, At least one tungsten compound selected from the group consisting of tungsten oxide, tungstic acid, and ammonium tungstate is used as the tungsten compound, and at least one molybdenum compound selected from the group consisting of molybdenum oxide, molybdic acid, and ammonium molybdate is used as the molybdenum compound, The method for producing a positive electrode active material for a lithium ion secondary battery is characterized in that a total amount of tungsten and molybdenum per 100 parts by mass of the base powder is adjusted to 0.1 to 6 parts by mass.

Citation Information

Patent Citations

  • Grain discharge auger of combine

    JP1988068022A

  • Positive electrode active material for lithium secondary battery, method for manufacturing the same and lithium secondary battery

    JP2012113823A

  • Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery

    JP2014041710A

  • Method of manufacturing active material powder

    JP2015201252A

  • Cathode material with excellent hardness and strength

    JP2017525089A